Model Integratif Protective Nudge dan Collaborative Policing dalam Safeguarding Keamanan Budaya Takbenda di Indonesia - Djuni Thamrin; Emi Winarno (Jurnal Keamanan Nasional, 2026)
The safeguarding of Intangible Cultural Heritage (ICH) has evolved beyond cultural preservation into a complex public governance challenge requiring coordinated action among governments, local communities, civil society organizations, academia, the private sector, and law enforcement agencies. Although the UNESCO 2003 Convention advocates community-centred safeguarding, existing studies largely conceptualize collaboration as an implementation mechanism rather than as an institutional governance architecture. This study addresses this gap by developing a Collaborative Multi-Stakeholder Governance Model (CMSGM) that institutionalizes collaborative governance for the sustainable safeguarding of ICH in Indonesia. A qualitative case study was employed using the Kebaya Goes to UNESCO initiative as the empirical context. Data were collected through five Focus Group Discussions, semi-structured interviews with 145 purposively and snowball-selected informants, participant observation, and documentary analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by triangulation and trustworthiness procedures. The findings reveal that effective ICH safeguarding depends on institutionalized collaboration rather than regulatory intervention alone. Community participation remains constrained by government-led decision-making, highlighting the need to reposition communities as co-producers of public value. The study further demonstrates that adaptive governance emerges through the integration of Collaborative Governance, Multi-Stakeholder Partnerships, Polycentric Governance, and Collaborative Policing, with the Indonesian National Police serving as a boundary-spanning institution that facilitates coordination, conflict mediation, and cultural security. The proposed CMSGM advances governance theory by shifting collaboration from a policy implementation mechanism to an institutional policy design. This study contributes to the literature on cultural governance by offering an integrative governance framework that strengthens legitimacy, collaborative capacity, and the long-term sustainability of living heritage, while providing practical guidance for public policy reform in Indonesia and other culturally diverse societies.